2001
DOI: 10.1002/cm.1042
|View full text |Cite
|
Sign up to set email alerts
|

Spindle positioning in fibroblasts supports an astral microtubule length dependent force generation at the basal membrane

Abstract: V79 Chinese hamster fibroblasts that maintain an elongated shape in metaphase occur at a low frequency and often show the spindle asymmetrically positioned. We show here that this aberrant position is corrected in anaphase by an external force, pulling the spindle into place. The force was applied on astral microtubules because spindle motility was hampered when astral microtubules were poorly developed spontaneously, or destroyed by colcemid. Colcemid also abolished the observed downward positioning of centro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Hemicentins were first identified in C. elegans , which contain a single representative called HIM-4 (Hodgkin et al, 1979). Subsequently, two vertebrate paralogues, Hemicentin-1 and Hemicentin-2, were identified (Schultz & Onfelt, 2001; Vogel et al, 2006). HIM-4 is secreted by skeletal muscles and gonad leader cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hemicentins were first identified in C. elegans , which contain a single representative called HIM-4 (Hodgkin et al, 1979). Subsequently, two vertebrate paralogues, Hemicentin-1 and Hemicentin-2, were identified (Schultz & Onfelt, 2001; Vogel et al, 2006). HIM-4 is secreted by skeletal muscles and gonad leader cells.…”
Section: Introductionmentioning
confidence: 99%
“…Observation of astral microtubules and spindle pole body movements have suggested that astral microtubules pull one spindle pole into the bud during budding yeast mitosis (Adames and Cooper 2000 ; Yeh et al 2000 ). In fibroblasts, astral microtubules transiently anchored at the bottom of the cell exert pulling forces to position the spindle (Schultz and Onfelt 2001 ). These mechanisms of pulling the organelles via cortically anchored molecular motors that move along astral microtubules can be described as “pulling” from the organelle viewpoint, and as “sliding” from the cortex perspective.…”
Section: Classification Of Microtubule-based Positioning Strategiesmentioning
confidence: 99%
“…In addition to this programmed genetic control of its positioning, the spindle is a dynamic structure that can reposition or realign within cells experiencing a variety of mutational or external perturbations [12]. Even in the highly orchestrated yeast cell cycle, old and new poles [13] as well as Kar9p can 'switch' from their predetermined fate if spindle positioning cues are abrogated [10].…”
mentioning
confidence: 99%